IMPORTANCE OF NATURAL COLORS OF FOOD IN HUMAN LIFE: भोजन के प्राकृतिक रंगो का मानव जीवन में महत्व - Bhana, Anita (International Journal of Research -GRANTHAALAYAH, 2014)
It is impossible to imagine life without colors. Rango has its own contribution in making life alive. Blue sky, gray earth, colorful fruits, flowers, animals, birds and green trees have faded in light of the progress of science and technology in the beauty of the color combination that God has made in nature. Food is the primary requirement of every living being, it has also been given a variety of colors like red yellow orange, blue purple green, black by nature and has made it more beautiful, approachable and attractive. Yellow color of papaya and mango, watermelon, red color of cherry, green color of spinach gilki or purple color of berries, these not only make food attractive but also relieve stress, depression and pain of human beings and make them mentally healthy. . The color of food items is also indicative of its quality and state of development. If the bright wheat color has changed to brown or gray, then the weather has definitely affected it. Green mango is raw, yellow mango is ripe and brown color indicates its over-ripening or rotting. The colors that nature has given to various food items have nutritious and medical importance as well. रंगो के बिना जीवन की कल्पना असंभव है। जीवन को जीवन्त बनाने में रंगो का अपना योगदान हैैैै। नीला आसमान, धूसर धरती, रंग बिरंगे फल-फूल, पशु पक्षियों व हरे भरे पेडों द्वारा ईश्वर ने प्रकृति मे जो रंग संयोजन किया है इसकी सुंदरता के आगे विज्ञान की प्रगति व तकनीक की चकाचैंध फीकी ही है। भोजन हर प्राणी की प्राथमिक आवश्यकता है इसे भी प्रकृति नें लाल पीले नारंगी, नीले जामुनी हरे, काले जैसे विविध रंगो से नवाजा है और उसे अधिक सुंदर, ग्राहय तथा मनमोहक बनाया है। पपीते व आम का पीला रंग,तरबूज, चेरी का लाल रंग, पालक गिलकी का हरा रंग हो या जामुन का जामुनी रंग ये न केवल भोजन को आकर्षक बल्कि मनुष्य के तनाव, अवसाद व पीड़ा को भी शांत कर उसे मानसिक रूप से स्वस्थ बनाते है। भोज्य पदार्थो का रंग उसकी गुणवत्ता तथा विकास की अवस्था का भी परिचायक होता है। गेहूं का चमकदार गेहूँआ रंग यदि भूरे या स्लेटी मे बदला है तो जरूर उस पर मौसम का कुप्रभाव पडा है। हरा आम कच्चा है पीला आम पका हुआ है व भूरा रंग उसके अधिक पके या सडे होने का संकेत देते है। प्रकृति ने जो रंग विविध भोज्य पदार्थों को दिये है उनका पौष्टिक व चिकित्सकीय महत्व भी है।